Injectable Peptide Hydrogel Enables Integrated Tandem Enzymes' Superactivity for Cancer Therapy - Wei, Qingcong; Jiang, Shan; Zhu, Rongrong; Wang, Xia; Wang, Shilong; Wang, Qigang (iScience, 2019)
Elevation of the levels of reactive oxygen species and other toxic radicals is an emerging strategy to treat certain cancers by modulating the redox status of cancer cells. The biocatalytic upregulation of singlet oxygen by neutrophilic leukocytes should utilize robust enzymes and design carriers with protective microenvironment. Here, we utilize GOx-CPO as integrated tandem enzymes to in situ generate singlet oxygen, which could be not only for oxidative cross-linking of injectable hydrogel carriers but also for continuous tumor treatment by adjustable bioconversion of blood oxygen, glucose, and chloride ion. The tandem enzymes self-restrained within peptide hydrogel exhibited superactivity for upregulating singlet oxygen relative to free enzymes, which also avoids the diffusion of enzymes from tumor. This work will not only deepen the study of enzymes in biocatalysis but also offer an enzyme therapeutic modality for treating cancers.